Analyse the Importance of Energy in Malaysia’s Economy and Diplomacy - Islam, Rabiul; Dharfizi, Awang Dzul-Hashriq; Pero, Siti Darwind Ahmed; Sultana, Sabina (International Journal of Energy Economics and Policy, 2022)
Due to the infrastructures needed to handle the LNG cargo, it is expected that the global LNG market will remain concentrated to countries that operate the liquefaction and regassification facilities in their ports, therefore resulting in an equally low export diversification destinations, in absence of sufficient intra-regional pipeline connection. The aim of this study is to what explains this situation, how it affects the supply-demand balance in the energy market and what can be done by Malaysia as an exporting country to further diversify the export destination to enhance the security of demand and its market access. Therefore, an optimal trade diversification model needs to be designed and developed to a mere handful of countries. This paper has been relied on primary and secondary data on qualitative approach through various official sources, interviews, observation and/or document analysis, published statistical data for the purposive sampling. The NVivo Qualitative Data Analysis Software (QDAS) has been used to facilitate the coding process and manage the coded data and organizing it into shared or similar themes across different documents. The paper shows the energy contributes significantly to Malaysia’s economy and Malaysia is more dependent on its LNG export to Japan and South Korea than the other way around, and generally trades of energy commodities are based on practical consideration. This can be done by comparing the diversification and concentration rate of export destinations among LNG exporting countries to establish a baseline or normative practice among LNG exporting countries for the purpose of comparison. The rising global conscience for cleaner energy sources has resulted in the increased LNG production in countries which previously have adopted the pipeline technology for gas delivery method. Malaysia’s LNG export destination have always been focused mainly on the East Asian countries, resulting in high export dependency.